Changes of pancreatic protein profile upon high fat diet intake in diabetic rat model - Teh, Ying-Hui; Sim, Xuan Yi; Sohaib Jumaah Owaid,; Mohd Nazri Ismail,; Gam, Lay-Harn (Penerbit Universiti Kebangsaan Malaysia, 2024)
The impact of a high-fat diet (HFD) on changes in pancreatic protein expression of the T2DM rat model was investigated. This is important as proteins are the functional components that regulate an organ’s activity. Adult male Sprague-Dawley rats were induced to diabetes using streptozotocin (STZ) and nicotinamide (NA). The diabetic rats and control rats were respectively fed with either a normal diet (ND) or a high-fat diet (HFD) that contained 39% fat for 6 consecutive weeks. The pancreases were harvested from the rats for proteomic analysis upon completion of the treatment period. Two-dimensional electrophoresis (2-DE) analysis was applied for protein separation and the significantly (p<0.05) upregulated protein spots in pair-wise comparison between different groups of rats were subjected to LC-MS/MS analysis for protein identification. The results showed that upregulation of anionic trypsin 1 and 2 in diabetic rats fed with ND compared to control rats fed with the same diet. The upregulation of these two proteins in diabetic rats acts as the defense mechanism against pancreatic tissue inflammation upon HFD intake. Moreover, upregulation of chymotrypsinogen B and transgelin-3 were detected in diabetic rats fed with HFD compared to those fed with ND, suggesting that these proteins may be induced by HFD intake, where upregulation of chymotrypsinogen B is a sign of pancreatic inflammation. Thus, HFD may influence specific pancreatic processes based on the observed protein changes.